Response surface methodology for the optimization of the production of rubber seed/palm oil biodiesel, IDI diesel engine performance, and emissions - Khalil, I. (Springer Verlag, 2017)
Emissions from diesel engines have been considered as major air pollution sources. The blending of feedstocks is motivated by the desire to enhance the properties and reduce the cost of biofuels. In this study, a rubber seed/palm oil mixture at equal blend ratios was used to produce biodiesel. The effects of irreverent parameters on transesterification were studied using the response surface methodology (RSM) to determine the maximum yield. Methyl ester at optimized conditions was produced, and its thermophysical properties were studied. Methyl ester effect on the emissions and performance of an unmodified indirect injection diesel engine (IDI) at partial and full load was examined. The results showed that the torque and brake mean effective pressure (BMEP) were 1.1 and 1 lower than diesel fuel, respectively. Compared to diesel fuel, power and brake thermal efficiency (BTE) were 1.1 and 1.3 lower, respectively, and the brake-specific fuel consumption (BSFC) was 1.4 higher at full load. CO was also reduced by 2 while CO2, NOx, and exhaust temperature increased on average by 1, 1.2, and 1.1 , respectively. © 2016, Springer-Verlag Berlin Heidelberg.